Sodium channel genes and the evolution of diversity in communication signals of electric fishes: Convergent molecular evolution - Zakon, Harold H. (National Academy of Sciences, 2006)
We investigated whether the evolution of electric organs and electric signal diversity in two independently evolved lineages of electric fishes was accompanied by convergent changes on the molecular level. We found that a sodium channel gene (Na(v)1.4a) that is expressed in muscle in nonelectric fishes has lost its expression in muscle and is expressed instead in the evolutionarily novel electric organ in both lineages of electric fishes. This gene appears to be evolving under positive selection in both lineages, facilitated by its restricted expression in the electric organ. This view is reinforced by the lack of evidence for selection on this gene in one electric species in which expression of this gene is retained in muscle. Amino acid replacements occur convergently in domains that influence channel inactivation, a key trait for shaping electric communication signals. Some amino acid replacements occur at or adjacent to sites at which disease-causing mutations have been mapped in human sodium channel genes, emphasizing that these replacements occur in functionally important domains. Selection appears to have acted on the final step in channel inactivation, but complementarily on the inactivation “ball” in one lineage, and its receptor site in the other lineage. Thus, changes in the expression and sequence of the same gene are associated with the independent evolution of signal complexity.